Learning the circulatory system through the learning management system-Moodle: How to develop teaching materials oriented towards scientific literacy? - Rusdi Rusdi; Anisa Fitria; ‪Rizhal Hendi Ristanto (Assimilation: Indonesian Journal of Biology Education, 2022)
Teaching materials are one of the important factors that determine the success of the learning process. The research objective was to develop a circulation system teaching material based on Moodle's LMS which is oriented towards increasing students' scientific literacy. The development model used was Thiagarajan 4D (Define, Design, Develop, and Disseminate), to the stage of feasibility testing (develop). The subjects in this study were validators of media experts, material experts, language experts, teachers and students. The data collection technique was carried out using a questionnaire to measure the validity of the open material. The results showed that the circulation system teaching materials based on the LMS-Moodle, which were oriented towards increasing scientific literacy, had an average score of 3.50 (very valid) from a maximum value of 4.00 from all aspects. Based on the results of the research, it is shown that the teaching materials of the circulation system based on the Moodle LMS which were developed to increase scientific literacy are very valid to be used as learning media for the circulation system in schools and are expected to improve students' scientific literacy.